ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR DI DAS KEDUANG JAWA TENGAH - Erlynda Kumalajati; Sambas Sabarnudi; Budiadi Budiadi; Putu Sudira (Jurnal Teknosains, 2015)
This study aims to examine the balance between the availability and water need in the present and the future in Keduang Watershed, Central Java. The water need is calculated by using the standard water need for irrigation and non-irrigation. Types of non-irrigation water need encompass the water need for domestic, office, and the facilities of health, education, religious duties, industry, and market, as well as livestock. The standard water need is from SNI 19-6728.1-2002 and Planning Criteria of Directorate General of Human Settlements of Department of Public Works in 1996. This study uses socio-economic data in 2013. The availability of water is calculated by using Soil Conservation Service Curve Number (SCS CN) from USDA with the hydrological data from 2005 to 2013. This study uses data in 2013, due to the limitations of the data that can be obtained. In the analysis of availability and water need, hydrological, and spatial data are projected until 2033 and analyzed using quantitative analysis in the form of descriptive statistics. The result shows that 1) from year to year in Keduang watershed, the water need is increasing with an average increase of 3.38%, while the water availability is decreasing with an average decrease of 0.09%. 2) Water deficit will begin in 2023, when the water need is reaching 115,306,568.00 m3/year, whereas the water availability only 112,250,656.00 m3/year. From this calculation, it can be concluded that if there is no effort to change the trend of land cover that lead to the goal of water conservation, then, the water availability will not able to cover the water need. Thus, in the future, Keduang watershed will occur water deficit.